Research on Acoustic Environment in the Building of Nursing Homes Based on Sound Preference of the Elderly People: A Case Study in Harbin, China - Cui, Peng; Zhang, Jun; Li, Ting Ting (Frontiers in Psychology, 2021)
Nursing homes are places where the elderly conduct their daily activities, and may lead to a complicated acoustic environment in which elderly people may have declining ability to function. In this study, the main indoor public space of a nursing home in Harbin was taken as the research object, and the methods of field observation, sound measurement and questionnaire survey were used to explore the sound perception and preference of the elderly. The results showed that in terms of temporal and spatial distribution of sound pressure level (SPL), the unit living space had highest SPL which was above 60dB(A). The reverberation time (RT) of unit living space, medical and health care center corridor were 2.15 s and 2.13 s respectively at the frequency of 1000Hz which was in discomfort range. The results also shown that there were great differences in speech articulation and speech intellibility in different spaces. Private space was better than open public space and narrow public space. Acoustic environment had strong correlation with humidity and weak correlation with temperature, but no significant correlation with luminous environment. The elderly were generally willing to accept the natural sound sources. The factors of gender and offspring numbers had no significant impact on the evaluation of acoustic environment comfort, while marriage and income status had. This study may help improve the quality of life of the elderly in the nursing home, and provide reference for the construction and design of pension facilities.